Assessment of Digital Economic Trade on Consumer - Rahman Mamoon, Zahidur (British Journal of Marketing Studies, 2016)
Increasing volumes of e-trade contribute to motivation of consumers to obtain commodities and services in electronic space. At the same time, upsurge of e-trade determines rising scopes of shadow economy in respect of favorable conditions for traders and service providers to operate in e-space evading taxpaying. The purpose of the article is to identify the factors of digital shadow consumption. In order to fulfill the defined purpose, the empirical research – survey of consumers (e-trade participants) – was performed. The research of the scientific literature has revealed that thus far the problem of consumers’ participation in digital shadow economy has been basically analyzed focusing on the impact of e-payment systems on shadow economy. Nevertheless, the rapid spread of e-services determines the changes in the concept of shadow economy itself. It remains indistinct which features indicate whether economic activities performed in e-space should be accounted or not. Widely exploited e-spaces such as social network platforms, alternative future currencies, e-trade systems, cyber computer games or online gambling terminals generate turnover of real money (or its electronic equivalent), which is not officially accounted. The problem raised in this article is highly topical for Lithuania, where online networks as well as mobile connection systems are comparatively advanced (with reference to the data of Lithuanian Department of Statistics, the number of households possessing a computer and the Internet access made over 65% in 2013). Intense exploitation of advanced IT technologies and online networks is considered as a breeding ground for generation of digital economy, a part of which is presumed to be digital shadow. The results of the research have revealed that the most significant factors of digital shadow consumption include lower prices of products and services in digital black markets, unfavorable economic situation in the country, technological advancement, IT advantages, time saving obtaining a product/service in the local market and lack of opportunities to obtain a desired product in the local market. The majority of the consumers neither verify the status of a trader nor request (or not always request) purchase confirmation documents, which highly contributes to motivation of an illegal trader to maintain e-activities unregistered, this way escaping revenue taxation.